A study of proton-induced reactions on natural Silicon targets - Nicolis, Nikolaos George; Zafeiri, Georgia (HNPS Advances in Nuclear Physics, 2023)
Experimental excitation functions of isotopes produced in reactions p + natSi are compared with the results of nuclear reaction program TALYS 1.95 and semi-empirical cross section formulas. We consider excitation functions of 7 isotopes (28Mg, 26Al, 24,22Na, 18F and 10,7Be) produced in reactions at bombarding energies of 20-144 MeV. They are compared with the predictions of the code TALYS 1.95, the semi-empirical formulas of Silberberg-Tsao (code yieldx) and SPACS. Comparisons of the results of the code TALYS 1.95 and previously published results of code ALICE are made. The predictive power of code TALYS 1.95 may be questioned for reaction products with mass number very much smaller than the target and of semi-empirical formulas at lower energies.